MAPEAMENTO DE FONTES SOBRE OS POVOS KADIWÉU E KINIKINAU, CENTRO-OESTE, BRASIL, (2000-2024) - Reginaldo, Gecica; Teixeira, Leia Lacerda; Andrade, Estela Mara de; Figueira, Kátia Cristina Nascimento (ANAIS DO ENIC, 2026)
.